Making YouTube videos - Willoughby, Nick, 1981-; Morris, Tee; Eagle, Will (Dummies Junior, 2020)
Written for kids in a language they can understand, this book helps budding filmmakers and producers create their own videos--no matter the subject. It offers creators the insight on how to plan and shoot quality videos, install and use video editing tools, and post the final product to YouTube.